Water-based resin for wall curing agent and preparation method of water-based resin
By introducing epoxidized nano SiO2 particles and aminolated lignin into the aqueous resin and crosslinking with the acrylic resin to form a stable network structure, the problem of insufficient adhesion and weatherability of the wall curing agent in extreme environments is solved, and the problem of insufficient adhesion and weather resistance of the wall curing agent in extreme environments is significantly Improves its adhesion, wear resistance and stain resistance.
Patent Information
- Application Number
- CN202411578772.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing wall curing agents have insufficient adhesion, wear resistance and weather resistance in extreme environments or long-term use, and are prone to peeling, bulging or aging, affecting aesthetics and functionality.
Using aqueous resin material, by mixing epoxidized nano SiO2 particles with aminolated lignin, the amino group and epoxy group react with isocyanate groups in the polyurethane prepolymer, enhance adhesion and structural strength, and add acrylic resin Conduct cross-linking reactions to form a stable network structure that resists ultraviolet rays and moisture.
It significantly improves the adhesion, wear resistance, weather resistance and stain resistance of the resin material, forms a more flexible, heat-resistant and ecologically friendly coating, and improves the overall performance of the wall curing agent.
Smart Images

Figure CN119220164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wall coatings, and particularly relates to a water-based resin for a wall curing agent and a preparation method thereof. Background Art
[0002] In the field of wall materials, existing curing agents are mainly used to enhance the adhesion, wear resistance and weather resistance of coatings, but in practical applications, these performances are still insufficient, especially in extreme environments or long-term use. For example, the coating of existing wall curing agents on some smooth or low-absorbency substrates is easy to peel off or fall off; especially in humid or dusty environments, the coating formed after curing is very easy to bulge or peel off. Therefore, it is urgent to improve the universal adhesion of curing agents on different substrates and the durability in special environments; secondly, in special application scenarios such as public buildings and industrial plants, the wall may be frequently rubbed, collided and scratched, and the coating is also easily damaged, causing the wall to lose its protective layer, thereby affecting its aesthetics and service life; furthermore, when the existing wall curing agents are used outdoors, due to their long-term exposure to sunlight, rain, wind and sand, and environments with large temperature changes, the coating is prone to aging, cracking, fading and other problems, which will not only affect the appearance of the wall, but also reduce the functionality of the coating, such as waterproof, mildew-proof, and anti-fouling properties. In summary, there is still much room for improvement in the adhesion, wear resistance, weather resistance and stain resistance of existing wall curing agents. Therefore, new resin materials are urgently needed to improve the performance of wall curing agents.
[0003] For example, Chinese patent CN107629627B discloses a new type of permeable hydrophobic multifunctional waterproof coating and its preparation method and application, which comprises the following components by weight: 30-45 parts of film-forming material, 4-8 parts of permeable waterproof hydrophobic raw materials, 0.3-0.6 parts of additives, 0.5-2 parts of permeable anti-corrosion agent, appropriate amount of pigment, 1-6 parts of thickener, 1-12 parts of active diluent, 3-6 parts of toughening agent, 30-45 parts of filler, and the amount of spirocyclic amine curing agent used is 30%-50% of the weight of the film-forming material. The waterproof coating has high bonding strength with concrete and large hydrophobic angle, has strong reinforcing waterproof effect, and is particularly suitable for concrete floors and walls with poor structural strength. However, the adhesion of the coating is greatly affected by environmental conditions (such as humidity and temperature), especially in high humidity or high temperature environments, the adhesion will decrease; and the film-forming material is not resistant to ultraviolet rays. After long-term exposure to sunlight, the coating will fade, powder or crack, reducing weather resistance. In summary, although the waterproof coating performs well in some aspects, it still has certain defects in adhesion, weather resistance and anti-fouling properties. Therefore, the present invention provides a water-based resin for wall curing agent and a preparation method thereof, in order to solve the above technical problems. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a water-based resin for wall curing agent and a preparation method thereof. In the preparation process of the water-based resin for wall curing agent, epoxidized nano-SiO2 particles are first mixed with amino lignin, and the amino and epoxy groups react with the isocyanate groups in the polyurethane prepolymer, thereby improving the adhesion and structural strength of the resin material; at the same time, the introduction of epoxidized nano-SiO2 particles in the present invention does not slow down the degradation process of lignin, but also enhances the hardness, heat resistance and wear resistance of the resin material, making the curing agent resin more durable in daily use; then, acrylic resin is added to cross-link with polyurethane to form a stable network structure, effectively isolate the influence of the external environment, reduce the attachment of pollutants, and resist ultraviolet and moisture damage, thereby significantly improving the adhesion, wear resistance, weather resistance and anti-fouling properties of the resin material.
[0005] A water-based resin for a wall curing agent comprises the following raw materials in parts by weight: 200-215 parts of polyurethane prepolymer, 100-110 parts of acrylic resin, 30-35 parts of amino lignin, 30-35 parts of epoxidized nano-SiO2 particles, 10-15 parts of polyamide, 5-6 parts of surfactant and 3-5 parts of catalyst.
[0006] A large number of hydrogen bonds can be formed between the amino groups (-NH) contained in the polyurethane prepolymer and the carboxyl groups (-COOH) in the acrylic resin, which can effectively enhance the binding force between the two. In addition, during the polymerization process, the double bonds (-C=C) of the acrylic resin can undergo a ring-opening reaction with the hydroxyl groups (-OH) in the polyurethane to form new covalent bonds. Therefore, when the two resins are mixed, the formation of the hydrogen bonds and covalent bonds causes the molecular chains to be cross-linked to form a complex three-dimensional network structure, which provides the system with excellent flexibility, adhesion, weather resistance and UV resistance. In addition, the cross-linked structure can effectively disperse stress and improve the mechanical properties of the overall resin material. Secondly, as a natural polymer resin material, the polymer structure and flexible molecular chain of amino lignin can assist the resin in forming a more flexible network after curing. Moreover, the phenolic hydroxyl group (-OH) in amino lignin can form hydrogen bonds with polyurethane and acrylic resin, further enhancing the adhesion and toughness of the resin material, and preventing the formation of micro-cracks on the surface, thereby reducing the possibility of dirt entering these micro-cracks. Therefore, introducing it into the resin used as a wall curing agent can effectively increase the toughness and elasticity of the resin, thereby improving the impact resistance of the resin material, while also enhancing the eco-friendliness of the resin material. Furthermore, the present invention also adds polyamide as a raw material, and its amide group (-CONH-) can form hydrogen bonds with polyurethane and acrylic resin to enhance the adhesion and toughness of the resin material. At the same time, its combination with amino lignin can form a composite phase in the resin, so that the applied external stress is effectively dispersed inside the resin material, preventing local overload and reducing the risk of cracking. In addition, the surface properties of the composite resin material are significantly improved due to the hydrophobicity of lignin and the wear resistance of polyamide, and a more uniform composite structure can be formed, so that the final coating surface is smoother, which can effectively prevent dirt from adhering, avoid the penetration of dirt on the surface and inside, and improve the cleanliness.
[0007] Furthermore, since lignin will show certain performance degradation under the conditions of high temperature, humidity or strong chemical corrosion, the present invention has modified the lignin and combined with raw materials such as modified epoxidized nano-SiO2 particles, which greatly reduces the degradation rate of lignin under a humid environment. Through an amination reaction, the present invention introduces an amino (-NH2) functional group on the surface of lignin, improves its compatibility with other components such as modified nano-SiO2 particles and resins, and the amination-treated lignin can form chemical crosslinks with polyurethane and acrylic resin, and the enhancement of compatibility can improve the stability of lignin in composite resin materials and slow down its degradation under high temperature, humidity or strong chemical corrosion environments.
[0008] Furthermore, the preparation of the amino lignin includes: dissolving lignin in ethanol, adding ethylenediamine, stirring and heating to 60-65°C for reaction for 4-6 hours, and after the reaction, washing the lignin product with distilled water, centrifuging and drying to obtain the amino lignin for later use.
[0009] The above-mentioned ethylenediamine reacts with the hydroxyl group of lignin to form amino lignin, so that the interaction between the lignin with the amino (-NH2) functional group and the modified epoxidized nano-SiO2 particles and the resin is enhanced, and the amino group reacts with the epoxy group to form a more stable chemical bond, which effectively improves the performance of lignin in the composite resin material; at the same time, the chemical interaction and physical cross-linking between the epoxidized nano-SiO2 particles and the amino lignin also significantly enhance the adhesion of the resin material to the wall substrate; moreover, the epoxy group can form a protective film in the resin to seal the active sites of the lignin, further slowing down its degradation in a strong chemical corrosion environment; and, the combination of the epoxidized nano-SiO2 particles and the polyurethane can effectively improve the stability of the resin material at high temperatures and slow down the thermal degradation of the lignin.
[0010] Furthermore, the mass ratio of lignin to ethylenediamine is (3-7): (1-2).
[0011] Furthermore, the preparation of the epoxidized nano-SiO2 particles includes: dispersing the nano-SiO2 particles in an ethanol solution, stirring and ultrasonically dispersing; then adding 3-aminopropyltriethoxysilane, stirring and reacting at room temperature for 3.5-4.5 hours, after the reaction is completed, centrifuging the product and washing it with ethanol, drying it for later use, and obtaining amino-modified nano-SiO2 particles; then re-dispersing the dried amino-modified nano-SiO2 particles in an ethanol solution, and then adding epichlorohydrin, stirring and reacting at 55-65°C for 4-6 hours, after the reaction is completed, centrifuging, washing with ethanol, and drying to obtain epoxidized nano-SiO2 particles.
[0012] In the above reaction, 3-aminopropyltriethoxysilane (APTES) reacts chemically with the hydroxyl groups on the surface of pretreated nano-SiO2 particles through its amino group to form amino-modified SiO2, which produces a silicon-oxygen bond (Si-O) chemical bond, which enhances the adhesion of nano-SiO2 to the resin matrix; then, epichlorohydrin (EPC) reacts with the surface of the amino-modified SiO2 particles to form a graft of epoxy groups, which provides additional reaction sites, so that the modified nano-SiO2 can be better cross-linked with polyurethane and acrylic resin, and the reaction of the final epoxy groups with active groups such as amino or hydroxyl groups can form a strong chemical bond (such as ether bond, etc.), further improving adhesion and durability. Moreover, the addition of the epoxidized nano-SiO2 particles of the present invention improves the overall waterproof performance and heat resistance of the resin material, and the epoxidized nano-SiO2 particles can form a dense network structure in the resin, reducing the penetration of water, thereby significantly reducing the degradation rate of lignin in a humid, high-temperature environment.
[0013] Furthermore, the usage ratio of the nano-SiO2 particles to 3-aminopropyltriethoxysilane and epichlorohydrin is (5-7) g: (1-2) g: (3-4) mL.
[0014] Furthermore, the surfactant is hexadecyltrimethylammonium bromide; and the catalyst is triethanolamine.
[0015] Moreover, the present invention also provides a method for preparing the water-based resin for wall curing agent as described above, comprising: adding epoxidized nano-SiO2 particles and amino lignin to an ethanol solvent, mixing, ultrasonically dispersing, and drying to obtain a mixture; then mixing a polyurethane prepolymer with the mixture at 60°C, and stirring for 1.5-2h; then adding an acrylic resin, and continuing to stir for 10-30min; adding polyamide, and stirring for 25-35min; adding a surfactant, and stirring for 10-15min; finally adding a catalyst, stirring for 15-30min, and standing for 0.5-1.5h to obtain the water-based resin for wall curing agent, and after eliminating bubbles, dispensing into sealed containers.
[0016] In the process of mixing epoxidized nano-SiO2 particles with amino lignin, the amino and epoxy groups therein can react with the isocyanate groups in the polyurethane prepolymer to form strong urea or carbamate bonds, which helps to improve the adhesion and structural strength of the resin material, and the introduction of epoxidized nano-SiO2 particles improves the hardness, heat resistance and wear resistance of the resin material, making the curing agent resin more durable in daily use; and the subsequent introduction of acrylic resin can react with the polyurethane to form a cross-linked structure, and a more stable network structure can be formed through polymerization, thereby effectively isolating the influence of the external environment, reducing the attachment of pollutants, and resisting the damage of ultraviolet rays and moisture, thereby improving the wear resistance, stain resistance and weather resistance of the resin material. In summary, the composite resin prepared by the present invention significantly improves the performance of the wall curing agent under various harsh conditions through a series of chemical reactions and cross-linking reactions, and solves the shortcomings of the existing curing agent resin materials.
[0017] Furthermore, the stirring speed is 400-700 rpm.
[0018] Secondly, the present invention also provides the use of the aqueous resin for wall curing agent as described above in the preparation of wall curing agent.
[0019] Compared with the prior art, the water-based resin for wall curing agent and the preparation method thereof provided by the present invention have the following advantages:
[0020] The composite resin of the present invention significantly improves the flexibility, adhesion, weather resistance and anti-fouling properties of the resin material by constructing a complex three-dimensional network structure. The interaction between the amino group (-NH) in the polyurethane prepolymer and the carboxyl group (-COOH) in the acrylic resin, coupled with the ring-opening reaction between the double bond (-C=C) of the acrylic resin and the polyurethane hydroxyl group (-OH), ensures the effective cross-linking of the molecular chain, thereby enhancing the overall mechanical properties of the resin material; and in order to enhance the eco-friendliness and toughness of the resin material, the amino lignin is introduced as a natural polymer resin material in the present invention, and the hydrogen bond formed between the phenolic hydroxyl group (-OH) and the resin not only improves the flexibility of the resin material, but also significantly reduces the formation of microcracks. At the same time, in order to enhance the stability of lignin in high temperature, humidity and chemical corrosion environments, the present invention treats lignin The lignin is modified and matched with modified epoxidized nano-SiO2 particles, which effectively improves the durability of lignin and its compatibility with other raw materials, makes the final resin coating surface smoother, and greatly enhances the cleanliness of the resin used as the wall curing agent; in addition, the present invention also introduces polyamide to further improve the adhesion and toughness of the composite resin material. The amide group (-CONH-) in the polyamide can form hydrogen bonds with polyurethane and acrylic resin, promote the effective dispersion of stress, and reduce the risk of cracking; and the modified epoxidized nano-SiO2 particles are modified by amino groups to provide additional reaction sites, thereby improving the heat resistance, waterproof performance and overall wear resistance of the resin, ensuring the excellent performance of the resin material under harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The water-based resin for the wall curing agent prepared in Example 3;
[0022] Figure 2 The water-based resin for the wall curing agent prepared in Example 2. DETAILED DESCRIPTION
[0023] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0024] In the following examples and comparative examples, the methods used are all prior art unless otherwise specified; the reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies. The information of some raw material manufacturers, CAS numbers, etc. is as follows:
[0025] Polyurethane prepolymer, purchased from Zibo Qishang Network Technology Co., Ltd.;
[0026] Acrylic resin, purchased from Changzhou Jienxin Resin Material Co., Ltd., brand JE-6132;
[0027] Lignin, CAS number is 8068-05-1;
[0028] Ethylenediamine, CAS number is 107-15-3;
[0029] 3-Aminopropyltriethoxysilane, CAS number 919-30-2;
[0030] Epichlorohydrin, CAS number is 106-89-8;
[0031] Polyamide, CAS No. 63428-84-2, purchased from Zhenjiang Danbao Resin Co., Ltd.;
[0032] Hexadecyltrimethylammonium bromide, CAS number 57-09-0;
[0033] Triethanolamine, CAS number is 102-71-6.
[0034] Example 1
[0035] (1) Preparation method of amino lignin: 300 g of lignin was dissolved in 2500 mL of ethanol, 100 g of ethylenediamine was added, and the mixture was stirred and heated to 60 °C for 4 h. After the reaction, the lignin product was washed with distilled water for 3 times, centrifuged and dried to obtain amino lignin.
[0036] (2) Preparation method of epoxidized nano-SiO2 particles:
[0037] Step ① Disperse 500g of nano-SiO2 particles in 50% ethanol solution, stir and disperse by ultrasound; then add 100g of 3-aminopropyltriethoxysilane, stir and react at room temperature for 3.5h. After the reaction is completed, centrifuge and wash the product with ethanol, and dry it to obtain amino-modified nano-SiO2 particles;
[0038] Step ②: Re-disperse the amino-modified nano-SiO2 particles obtained in step ① in a 50% ethanol solution, then add 300 mL of epichlorohydrin, stir and react at 55°C for 4 hours, and after the reaction, centrifuge, wash with ethanol 3 times, and dry to obtain epoxidized nano-SiO2 particles.
[0039] (3) Preparation method of water-based resin for wall curing agent:
[0040] 300g of epoxidized nano-SiO2 particles and 300g of amino lignin are added to an ethanol solvent, mixed, ultrasonically dispersed and dried to obtain a mixture; then, 2000g of polyurethane prepolymer is mixed with the above mixture at 60°C, and stirred at a speed of 400 rpm for 1.5h; then 1000g of acrylic resin is added, and stirring is continued for 10min; 100g of polyamide is added, and stirring is continued for 25min; 50g of hexadecyltrimethylammonium bromide is added, and stirring is continued for 10min; finally, 30g of triethanolamine is added as a catalyst, and stirring is continued for 15min. The mixture is allowed to stand for 0.5h to obtain a water-based resin for wall curing agent. After eliminating bubbles, it is divided into sealed containers.
[0041] Example 2
[0042] (1) Preparation method of amino lignin: 700 g of lignin was dissolved in 2500 mL of ethanol, 200 g of ethylenediamine was added, and the mixture was stirred and heated to 65 °C for 6 h. After the reaction, the lignin product was washed with distilled water for 3 times, centrifuged and dried to obtain amino lignin.
[0043] (2) Preparation method of epoxidized nano-SiO2 particles:
[0044] Step ① Disperse 700g of nano-SiO2 particles in 50% ethanol solution, stir and disperse by ultrasound; then add 200g of 3-aminopropyltriethoxysilane, stir and react at room temperature for 4.5h. After the reaction is completed, centrifuge and wash the product with ethanol, and dry it to obtain amino-modified nano-SiO2 particles;
[0045] Step ②: Re-disperse the amino-modified nano-SiO2 particles obtained in step ① in a 50% ethanol solution, then add 400 mL of epichlorohydrin, stir and react at 65°C for 6 hours, and after the reaction, centrifuge, wash with ethanol three times, and dry to obtain epoxidized nano-SiO2 particles.
[0046] (3) Preparation method of water-based resin for wall curing agent:
[0047] Add 350g of epoxidized nano-SiO2 particles and 350g of amino lignin into an ethanol solvent, mix, ultrasonically disperse and dry to obtain a mixture; then, at 60°C, mix 2150g of polyurethane prepolymer with the above mixture, and stir at 700 rpm for 2h; then add 1100g of acrylic resin, and continue stirring for 30min; add 150g of polyamide, and continue stirring for 35min; add 60g of hexadecyltrimethylammonium bromide, and then stir for 15min; finally, add 50g of triethanolamine as a catalyst, stir for 15-30min, and let stand for 1.5h to obtain a water-based resin for wall curing agent. After eliminating bubbles, divide it into sealed containers.
[0048] Example 3
[0049] (1) Preparation method of amino lignin: 500 g of lignin was dissolved in 2500 mL of ethanol, 150 g of ethylenediamine was added, and the mixture was stirred and heated to 60 °C for 5 h. After the reaction, the lignin product was washed with distilled water for 3 times, centrifuged and dried to obtain amino lignin.
[0050] (2) Preparation method of epoxidized nano-SiO2 particles:
[0051] Step ① Disperse 600g of nano-SiO2 particles in 50% ethanol solution, stir and ultrasonically disperse; then add 150g of 3-aminopropyltriethoxysilane, stir and react at room temperature for 4h. After the reaction is completed, centrifuge and wash the product with ethanol, and dry it to obtain amino-modified nano-SiO2 particles;
[0052] Step ②: Re-disperse the amino-modified nano-SiO2 particles obtained in step ① in a 50% ethanol solution, then add 350 mL of epichlorohydrin, stir and react at 60°C for 5 hours, and after the reaction, centrifuge, wash with ethanol three times, and dry to obtain epoxidized nano-SiO2 particles.
[0053] (3) Preparation method of water-based resin for wall curing agent:
[0054] 350g of epoxidized nano-SiO2 particles and 300g of amino lignin are added to an ethanol solvent, mixed, ultrasonically dispersed and dried to obtain a mixture; then, 2100g of polyurethane prepolymer is mixed with the above mixture at 60°C, and stirred at a speed of 500 rpm for 2h; then 1100g of acrylic resin is added, and stirring is continued for 20min; 150g of polyamide is added, and stirring is continued for 30min; 55g of hexadecyltrimethylammonium bromide is added, and stirring is continued for 15min; finally, 40g of triethanolamine is added as a catalyst, and stirring is continued for 20min. The mixture is allowed to stand for 1h to obtain a water-based resin for wall curing agent. After eliminating bubbles, the resin is dispensed into sealed containers.
[0055] Comparative Example 1
[0056] The difference from Example 3 is that no amino lignin is added in Comparative Example 1, and the other steps and preparation process are the same as those of Example 3.
[0057] Comparative Example 2
[0058] The difference from Example 3 is that, in Comparative Example 2, the lignin is not modified; the other steps and preparation process are the same as those of Example 3.
[0059] Comparative Example 3
[0060] The difference from Example 3 is that no epoxidized nano-SiO2 particles are added in Comparative Example 3, and the other steps and preparation process are the same as those of Example 3.
[0061] Comparative Example 4
[0062] The difference from Example 3 is that in Comparative Example 4, the nano-SiO2 particles are not modified, and the other steps and preparation processes are the same as those of Example 3.
[0063] Comparative Example 5
[0064] The difference from Example 3 is that no polyamide is added in Comparative Example 5, and other steps and preparation processes are the same as those of Example 3.
[0065] Comparative Example 6
[0066] The difference from Example 3 is that the amount of polyurethane prepolymer used in Comparative Example 6 is 1100 g, and the other steps and preparation process are the same as those in Example 3.
[0067] Test example: performance test
[0068] 1. Test resin material: water-based resin used in the wall curing agent prepared in the examples and comparative examples of the present invention.
[0069] 2. Test methods:
[0070] (1) Test the stain resistance of the sample in accordance with GB / T9780-2013 "Test method for stain resistance of architectural coatings";
[0071] (2) Test the cross-cut adhesion of the sample in accordance with GB / T9286-1998 “Cross-cut test for paint and varnish films”;
[0072] (3) Test the flexibility of the sample according to GB / T1731-2020 “Determination of flexibility of paint film and putty film”;
[0073] (4) Test the impact resistance of the sample in accordance with GB / T1732-2020 “Determination of impact resistance of paint film”;
[0074] (5) Test the water resistance of the sample in accordance with GB / T1733-1993 “Determination of water resistance of paint film”;
[0075] (6) Test the sample's salt spray resistance for 1000h in accordance with GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes";
[0076] (7) Test the pencil hardness of the sample in accordance with GB / T6739-2006 “Determination of film hardness of paints and varnishes by pencil method”.
[0077] The test results are shown in Table 1 and Table 2.
[0078] Table 1 Performance test results of the embodiment of the present invention
[0079]
[0080] Table 2 Performance test results of comparative examples of the present invention
[0081]
[0082] As shown in the above test results, the performance test results of the water-based resin for wall curing agent obtained in the embodiment of the present invention are excellent. When the raw materials and preparation parameters in the preparation process of the present invention are changed in each group of comparative examples, the performance of the obtained resin material is affected to varying degrees.
[0083] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A water-based resin for a wall curing agent, characterized in that: The invention comprises the following raw materials in parts by weight: 200-215 parts of polyurethane prepolymer, 100-110 parts of acrylic resin, 30-35 parts of amino lignin, 30-35 parts of epoxidized nano-SiO2 particles, 10-15 parts of polyamide, 5-6 parts of surfactant and 3-5 parts of catalyst.
2. The water-based resin for wall curing agent according to claim 1, characterized in that: The preparation of the amino lignin comprises: dissolving lignin in ethanol, adding ethylenediamine, stirring and heating to 60-65° C. for reaction for 4-6 hours, and after the reaction, washing the lignin product with distilled water, centrifuging and drying to obtain the amino lignin.
3. The water-based resin for wall curing agent according to claim 2, characterized in that: The mass ratio of the lignin to ethylenediamine is (3-7):(1-2).
4. The water-based resin for wall curing agent according to claim 1, characterized in that: The preparation of the epoxidized nano-SiO2 particles comprises: Step ① Disperse nano-SiO2 particles in an ethanol solution, stir and ultrasonically disperse; then add 3-aminopropyltriethoxysilane, stir and react at room temperature for 3.5-4.5 hours. After the reaction is completed, centrifuge and wash the product with ethanol, and dry it to obtain amino-modified nano-SiO2 particles; Step ②: Re-disperse the amino-modified nano-SiO2 particles in an ethanol solution, then add epichlorohydrin, stir and react at 55-65°C for 4-6 hours, and after the reaction, centrifuge, wash with ethanol, and dry to obtain epoxidized nano-SiO2 particles.
5. The water-based resin for wall curing agent according to claim 4, characterized in that: The usage ratio of the nano-SiO2 particles to 3-aminopropyltriethoxysilane and epichlorohydrin is (5-7) g: (1-2) g: (3-4) mL.
6. The water-based resin for wall curing agent according to claim 1, characterized in that: The surfactant is hexadecyltrimethylammonium bromide; and the catalyst is triethanolamine.
7. The method for preparing the water-based resin for a wall curing agent according to any one of claims 1 to 6, characterized in that: include: Add epoxidized nano-SiO2 particles and amino lignin to an ethanol solvent, mix, ultrasonically disperse, and dry to obtain a mixture; then, mix the polyurethane prepolymer with the mixture at 60°C and stir for 1.5-2h; then add acrylic resin and continue stirring for 10-30min; add polyamide and stir for 25-35min; add surfactant and stir for 10-15min; finally, add catalyst and stir for 15-30min, let stand for 0.5-1.5h to obtain a water-based resin for wall curing agent, and dispense into sealed containers after eliminating bubbles.
8. The method for preparing the water-based resin for wall curing agent according to claim 7, characterized in that: The stirring speed is 400-700 rpm.
9. Use of the aqueous resin for wall curing agent as claimed in any one of claims 1 to 6 in the preparation of wall curing agent.
Citation Information
Patent Citations
Preparation method, product and application of modified chitosan-nano-silica hybrid adsorbent
CN110314660A
Durable self-repairing building coating and preparation method thereof
CN110564257A
Polypropylene composite material and preparation method thereof
CN112126153A
Aqueous coating composition and method for forming multilayered coating film
CN113646096A
Self-crosslinking exterior wall coating containing reinforced fibers and preparation method of self-crosslinking exterior wall coating
CN117965071A